Ecofriendly synthesis and solar photocatalytic activity of S-doped ZnO - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Hazardous Materials, 2010)
The S-doped ZnO was prepared by new ecofriendly method, which involves simple mechanochemical synthesis followed by thermal decomposition of bisthiourea zinc oxalate (BTZO) powders. The BTZO was characterized by FTIR and TG-DTA analysis while S-doped ZnO crystallite was characterized by XRD, XPS, SEM, EDXS, and photoluminescence (PL) spectra. X-ray diffraction data suggest the single phase wurtzite structure for S-doped ZnO and the incorporation of sulfur expand the lattice constants of ZnO. Room temperature PL spectra show more number of oxygen vacancies in S-doped ZnO as compare to that of pure ZnO. Photocatalytic activity of S-doped ZnO was checked by means of solar photocatalytic degradation (PCD) of resorcinol, using a batch photoreactor. The PCD efficiency of S-doped ZnO was found to be 2 times greater than that of pure ZnO. The inherent relationship between PL intensity and photocatalytic activity of S-doped ZnO was discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Photocatalysis; photoluminescence; Resorcinol; S-doped ZnO; Sunlight; XPS

Solvent-free coumarin synthesis via pechmann reaction using solid catalysts - Kalita, Pranjal; Kumar, Rajiv (Microporous and Mesoporous Materials, 2012)
A solvent-free versatile and efficient methodology, reported here, allows the synthesis of coumarin by hydroxyalkylation of phenols with ethyl or methyl acetoacetate (via Pechmann reaction) using trifluoromethanesulfonic acid (trifle acid) functionalised Zr-TMS (Zr-TMS, zirconia based transition metal oxide mesoporous molecular sieves) catalysts with different loadings of triflic acid over Zr-TMS (5-25 wt.%) where the total acid strength of acid functionalised Zr-TMS material is increased as increasing loading of triflic acid from 5 to 25 wt.% leading to correspond increased higher catalytic activity. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Coumarin; Ethyl acetoacetate; Functionalization; Pechmann reaction; Resorcinol; Zr-TMS

Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol

Adsorptive removal of chromium(VI) using spherical resorcinol-formaldehyde beads prepared by inverse suspension polymerization - Mulani, Khudbudin; Patil, Vishwanath; Chavan, Nayaku; Donde, Kamini (Journal of Polymer Research, 2019)
The spherical cross-linked beaded polymers were prepared by condensation of resorcinol and formaldehyde in presence of tri-ethylamine by inverse suspension polymerization technique. The m-cresol, aniline, urea and thiourea were used as co-monomer and polyethylene glycol (PEG 400) was used as porogen. Paraffin oil was used as non-aqueous suspension agent. The polymeric spherical beads were prepared using various types of comonomers exhibiting range of particle size 77.62 to 158.84m at 90 degrees C and 300rpm for 4h. The resulting beads were analyzed by elemental analysis, particle size analysis and scanning electron microscope (SEM). The synthesized beads were used for the removal of Cr(VI) from aqueous solutions. A simple and sensitive solid phase extraction procedure was used for the determination of chromium at trace level by spectrophotometric method using 1,5-diphenylcarbazide reagent. The adsorption of Cr(VI) on the resorcinol-formaldehyde beads was monitored by energy-dispersive X-ray spectroscopy (EDX) analysis. The metal adsorption parameters such as contact time, pH, metal ion concentration and adsorbent dose were investigated. For Cr(VI), the maximum adsorption capacity was about 99% at pH2 for the resorcinol-formaldehyde beads obtained.
Keywords: adsorption kinetics; Beads; Chromium (VI); Formaldehyde; Inverse suspension; Resorcinol